Impact of the preprocedural nutrition status on the clinical outcomes of patients after pacemaker implantation for bradycardia. Issue 3 (September 2019) - Yamaguchi, Tetsuo; Nozato, Toshihiro; Miwa, Naoyuki; Sagawa, Yuichiro; Watanabe, Keita; Nagata, Yasutoshi; Miyazaki, Ryoichi; Mitsui, Kentaro; Nagase, Masashi; Nagamine, Tatsuhiro; Yamaguchi, Junji; Masuda, Ryo; et al.
Highlights: Preprocedural malnutrition is associated with poor all-cause mortality. The geriatric nutritional risk index is a simple and established method. Coexisting cancer is another important predictor for all-cause death. Assessing the nutritional status in advance is important for risk stratification. Improving the nutritious status may be an option for managing these patients. Abstract: Background: Malnutrition is associated with a poor prognosis in heart failure, angina pectoris, and peripheral artery disease. However, the clinical importance of the preprocedural nutrition status of patients requiring pacemaker implantation (PMI) for bradycardia is unclear. Methods: We retrospectively enrolled 521 patients (median 79 years) who underwent their first PMI between January 1, 2012 and June 30, 2017. The nutrition status before implantation was assessed by the geriatric nutritional risk index (GNRI). The association between the preprocedural GNRI-based nutritional status and all-cause mortality was investigated. Results: GNRI-based high (GNRI <82) and moderate (GNRI 82 to <92) malnutrition status were found in 9.2% and 34.0%, respectively. During a median follow-up of 1178 days, 71 patients died. The mortality rate, which was analyzed using survival curves, was significantly stratified by the GNRI-based malnutrition status [high: 52.0% (25/48), moderate: 16.9% (30/177), low: 5.4% (16/296), p < 0.001). On a multivariate Cox-proportional hazard analysis, GNRI-based high malnutrition status independently predicted all-cause death (hazard ratio: 4.49, 95% confidence interval: 2.59–7.80, p < 0.001). A sensitivity analysis based on the controlling nutritional status score showed consistent results. On a receiver operating characteristic curve analysis, GNRI had a high predictive value for all-cause mortality (area under the curve, 0.78, 95% confidence interval: 0.72–0.84, p < 0.001). Conclusions: Preprocedural malnutrition was significantly associated with poor outcomes of patients who underwent PMI. Assessing the nutritional status in advance is important for risk stratification, and improving the nutritional status may be an option for managing these patients.